Development of Intensity-Duration-Frequency Curves of Intense Rainfall With Emphasis on the Behavior of the Upper Tail of the Distribution - Pansera, Wagner Alessandro; Gomes, Benedito Martins; de Mello, Eloy Lemos; Saad, João Carlos Cury [UNESP] (FapUNIFESP (SciELO), 2022)
The design and management of various hydraulic structures (such as stormwater drains, bridges and dams) require the estimation of rainfall with duration of a few minutes up to 24 h or more. Intensity-duration-frequency (IDF) curves links probability of occurrence to a given rainfall intensity. The procedure for obtaining IDF curves basically involves two steps: (i) frequency analysis for different durations and (ii) modeling of IDF curves. In the first step, this study aimed to adequately select the upper tail weight of the following distributions: generalized extreme value (GEV), generalized logistic (GLO) and generalized Pareto (GPA). In the second step, this study aimed to evaluate the performance of three models of IDF curves. The traditional model (M1) was compared with empirical model (M2) and a second-order polynomial model (M3). To perform this study, rainfall data from the city of Caraguatatuba (São Paulo state, Brazil) for the period between 1971 and 2001 were used, for time intervals between 10 and 1440 min. The main conclusions were: (i) GLO and GEV had heavy upper tail while GPA had light upper tail, impacting quantiles with T > 100 years; (ii) M3 presents errors lower than M1 for return periods greater than 100 years.
Desenvolvimento de Curvas de Intensidade-Duração-Frequência de Chuvas Intensas com Ênfase no Comportamento da Cauda Superior da Distribuição
Keywords: design rainfall; extreme values; LH moments